Discuss the Influence and Optimization of Consolidated Statements on Group Financial Management - Liu, Lipeng (Journal of Theory and Practice of Social Science, 2023)
This paper focuses on the positive and negative impacts of consolidated statements on corporate financial management and the optimization to carry out in-depth research. First, it briefly discusses the basic concept of consolidated financial statements, comprehensively analyzes its role and constraints on corporate financial management, and puts forward feasible optimization and improvement strategies to improve the information quality of consolidated statements, strengthen financial management, and promote corporate sustainability Continue to develop.